Rancang Bangun Sistem Informasi Peramalan Bisnis pada Berkah Swalayan - Muhammad Aly Al-Husaini (UIN Sultan Syarif Kasim Riau, 2018)
Berkah Supermarkets is one of the small and medium enterprises (SMEs) that sells various types of goods including food and soft drinks. According to interviews conducted it turns out that the company has difficulty predicting sales, planning purchases, and managing inventory. Therefore, a business forecasting information system for Berkah Supermarket is built. Forecasting uses the single exponential smoothing method and the trend analysis method. The forecasting method is chosen based on data patterns and calculations with the Minitab application. The process of purchasing planning and inventory management is done by calculating the value of Economic Order Quantity (EOQ), Reorder Point (ROP), and Safety Stock (SS). The data used is sales data of various types of soft drinks and foods. The output of this system is sales prediction information, economic purchases, and minimal inventory. Based on black box testing, it was found that the system was 100% running well. Based on white box testing, the results of the program code execution percentage are 100%. Based on the accuracy testing the forecasting method is produced that 8 out of 10 items using the trend analysis method and 2 in 10 items using the single exponential smoothing method. Based on the forecasting error level testing produced that Biskuat Coklat has the highest forecasting error rate of 50% and Roma Kelapa has the smallest error rate of 0%. Keywords: information system, forecasting, sales, minitab, single exponential smoothing, trend analysis